Antimicrobial potential of various solvent extracts from leaf, stem and root of Raja Berangkat (Anisophyllea disticha) - Abdul Bari, Nurul Ashikin; Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Shahari, Rozilawati (2016)
Raja Berangkat (Anisophyllea disticha) is a plant that has been utilized by folklore medicine for treating diarrhea, dysentery and fever where these symptoms can be associated with pathogenic infections like bacteria and virus. Thus this study was designed to examine the antimicrobial capability of various solvent extracts from leaf, stem and root of A. disticha against bacterial strains that included Escherichia coli, Enterococcus aerogenes, Staphylococcus aureus and Staphylococcus epidermidis. Successive soxhlet extraction was performed using hexane, dichloromethane and methanol with highest yield was recorded for the extraction of leaf in methanol with the value of 4.85%. It was further noted the extract yields in descending order followed this trend: methanol > dichloromethane > hexane for all the plant parts. Phytochemical screening conducted proved the presence of phenols, steroids as well as saponins in A. disticha. Based on antimicrobial assay by disc diffusion method (200, 400 and 600 µg/disc), leaf extracted using methanol exhibited potent growth inhibitory activity against S. epidermidis with a diameter of 7.67±0.58 mm. The results showed that methanol extraction was more efficient in extracting bioactive compounds in leaf, stem and root of A. disticha. Therefore, the result supports that these plant extracts can be used for the treatment of bacterial infections.